Murine mutants in the study of systemic iron metabolism and its disorders: an update on recent advances - Bartnikas, Thomas B. (2012)
Many past and recent advances in the field of iron metabolism have relied upon the use of mouse models of disease. These models have arisen spontaneously in breeder colonies or have been engineered for global or conditional ablation or overexpression of select genes. Full phenotypic characterization of these models typically involves maintenance on iron-loaded or – deficient diets, treatment with oxidative or hemolytic agents, breeding to other mutant lines or other stresses. In this review, we focus on systemic iron biology and the contributions that mouse model-based studies have made to the field. We have divided the field into three broad areas of research: dietary iron absorption, regulation of hepcidin expression and cellular iron metabolism. For each area, we begin with an overview of the current understanding of key molecular and cellular determinants then discuss recent advances. Finally, we conclude with brief comments on prospects for future study.